Real-time crime detection using convolutional LSTM and YOLOv7 - Sakiba, Cyrus; Tarannum, Syeda Maisha; Nur, Farzana; Arpan, Fahad Faisal; Anzum, Ahnaf Ahmed (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.